Implementasi Secure Tunnel pada Peering BGP untuk Mitigasi Serangan Man-in-the-Middle di Jaringan TCP/IP - Surono; Agus Hartanto; Galih Setiarso; Krida Pandu G (JITU, 2026)
The Border Gateway Protocol (BGP), as the core internet routing protocol, lacks built-in security mechanisms, making it vulnerable to Man-in-the-Middle (MITM) attacks and sniffing. This research aims to test the effectiveness of an OpenVPN-based secure tunnel in enhancing the security of BGP peering sessions while analyzing its impact on network performance. The method used is an experiment with a pre-test and post-test design, comparing conditions before and after OpenVPN implementation between two routers on different platforms (Linux/FRRouting and MikroTik RouterOS). Test results show that OpenVPN successfully secures BGP communication by encrypting all traffic, thereby eliminating the risk of plaintext reading and passive MITM attacks. However, this implementation introduces a performance trade-off: latency increases by 2.6 ms (50%), throughput decreases by 289 Mbps (30.6%), and CPU utilization surges up to 60% due to encryption overhead. Nonetheless, BGP session stability is maintained with 99.95% uptime. The research concludes that OpenVPN is an effective solution for securing BGP in high-risk environments, with the caveat that hardware capacity and bandwidth requirements must be evaluated to minimize performance overhead impact.